(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
This paper outlines a study of meaning-giving and especially subjectification as a social enterprise, an enterprise that Michel Foucault denotes ’power’. Power is considered an ongoing social game that determines not only what things are, but also who and what we are, i.e. ’subjectification’. By looking at how we become, who we are from a social perspective, our understanding of meaning giving and creation of identity is not only broadened, it also enables us, as existential therapists to help the clients understand and resist these games of power. The freedom to define her- or himself differently is enhanced.